The State and Pattern of Health Information Technology Adoption - Fonkych, Katya (RAND Corporation, 2005)
Helps focus the policy agenda for incentives to speed Healthcare Information Technology (HIT) adoption by estimating the current level and pattern of HIT adoption in the different types of healthcare organizations, according to information the Healthcare Information and Management Systems Society (HIMSS)-Dorenfest database, and evaluates factors that affect this diffusion process, using existing empirical studies and regression analysis.